URGENSI PENDIDIKAN KEWARGANEGARAAN DALAM MEMBENTUK KARAKTER BANGSA YANG TANGGUH DI ERA DIGITAL - Gregoriana Martina Faot; Fadil Mas’ud; Jermy I. Balukh; Gupuh Rahayu (STKIP Subang, 2026)
This research aims to analyze the urgency of Civic Education (Pendidikan Kewarganegaraan/PKn) in the context of the digital era to build a resilient national character. The massive development of information technology has brought new challenges to national identity and cohesion, such as the spread of disinformation and the potential for disintegration. Civic Education plays a crucial role as a vehicle for instilling Pancasila values, patriotism, and digital-civic literacy. The method used is a literature review (library research) with a descriptive-qualitative approach, analyzing various primary and secondary sources related to Civic Education and digital challenges. The results of the study indicate that Civic Education must transform into a Digital Ecosystem and National Narrative that focuses on strengthening virtual public ethics and digital citizenship competence. The implementation of adaptive and holistic Civic Education is expected to produce good and smart citizens who are capable of interacting in the digital space while upholding the nation's noble values, thereby forming a resilient national character.